A new species of Lepidotrigla from the South China Sea off Vietnam (Teleostei: Scorpaeniformes: Triglidae) - Prokofiev, Artem M.; Yato, Takuji (Zootaxa, 2020)
A new species of the gurnard genus Lepidotrigla is described from the South China Sea off southernmost central Vietnam. Lepidotrigra firmisquamis sp. nov. is most similar to L. alata and L. marisinensis and co-occurs with L. marisinensis in the Bays of Nha Trang and Van Phong, but can be easily distinguished from both species by the well developed preocular spines and postorbital groove and by a slightly lower lateral-line scale count (54–58 instead of 58–64). A comparison with all Lepidotrigla species known from the South China Sea is presented.